Κατασκευαστικές λεπτομέρειες μεταλλικής κατασκευής - Νικολαΐδου, Στυλιάνα (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικης, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
The compelling needs of modern construction for easy, fast, flexible, innovative, creative, attractive and at the same time elegance solutions, promoted the construction of steel structures. These requirements and properties of structural steel, which allow steel to be used in a wide range of applications, helped steel structures to establish and develop solutions which are offering high aesthetics. This thesis, through a wide range of manufacturing of metal structures, reviews the most important aspects of structure of steel buildings and presents typical construction details of factors that involved in a metal building. To carry out this study, there was a research on the study subject in books and trusted websites. Due to the technical nature of the study, the sources from where information received were limited. Furthermore, during the survey and appraisal of information, there where appointments with Civil Engineers and companies engaged in steel building construction, for information and material. Specifically, Chapter 1 gives a general description of metals and mainly for the use of structural steel in building construction, whereas Chapter 2 gives the main ways in foundation and construction of supporting structure of a steel building. Chapter 3 indicates the main types of connections between beams and columns, Chapter 4 presents the most common type of coating of a metal construction and Chapter 5 referred some of the secondary metal structures. Finally, Chapter 6 describes the main elements of erecting steel buildings, ways to protect them from fire and indicates some typical static drawings of steel buildings construction projects in Cyprus.
Keywords: Structural steel; Metal; Steel; Μεταλλικές Κατασκευές; Μέταλλα; Χάλυβας